2020
DOI: 10.1128/aem.01165-20
|View full text |Cite
|
Sign up to set email alerts
|

Differential Modulation of Listeria monocytogenes Fitness, In Vitro Virulence, and Transcription of Virulence-Associated Genes in Response to the Presence of Different Microorganisms

Abstract: Interactions between Listeria monocytogenes and food-associated or environmental bacteria are critical not only for the growth but also for a number of key biological processes of the microorganism. In this regard, limited information exists on the impact of other microorganisms on the virulence of L. monocytogenes. In this study, the growth of L. monocytogenes was evaluated as single culture or in co-culture with L. innocua, Bacillus subtilis, Lactobacillus plantarum and Pseudomonas aeruginosa in tryptic soy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…The adhesion and invasion abilities of L. monocytogenes to Caco-2 cells are reduced when L. monocytogenes is co-cultured with Lactobacillus spp. [ 68 ], Lactobacillus rhamnoides [ 69 ], and L. plantarum [ 55 ]. Moroni et al observed that the adhesion and invasion ability of L. monocytogenes to colonocytes was reduced by Lactobacillus [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The adhesion and invasion abilities of L. monocytogenes to Caco-2 cells are reduced when L. monocytogenes is co-cultured with Lactobacillus spp. [ 68 ], Lactobacillus rhamnoides [ 69 ], and L. plantarum [ 55 ]. Moroni et al observed that the adhesion and invasion ability of L. monocytogenes to colonocytes was reduced by Lactobacillus [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…All assays were independently repeated six times. Most previous reports used 1–2 h to detect the in vitro adhesion and invasion [ 55 ], so we used 1, 1.5, and 2 h for evaluation, and 2 h was the shortest time to detect the difference among different treatment groups.…”
Section: Methodsmentioning
confidence: 99%
“…The pathogenic potential of L. monocytogenes, assessed almost exclusively by invasion to cell lines, such as Caco-2, THP-1 and HT-29, is affected by abiotic and biotic stimuli that include exposure to temperature, acid and osmotic fluctuations as well as the food matrix and co-existing microorganisms [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Correlation between the transcriptomic response of the pathogen to the above stresses with invasiveness, in some cases was successful [13,21]. Several studies have assessed the transcription of virulence associated genes during growth of L. monocytogenes on a food matrix at various storage temperatures and times [8][9][10][11][12][13][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…More accurately, Olesen et al [8], Bae et al [9], Rantsiou et al [10,11] and Mataragas et al [12] studied the transcription of key virulence genes of the pathogen on meat products, Duodu et al [13] and Pilevar et al [14] on fish products, Rantsiou et al [11] and Alessandria et al [15] on dairy products and Hadjilouka et al [16] and Kang et al [17] on fruits and vegetables. The significance of these studies is highlighted by the fact that prior exposure to environmental stimuli affects invasiveness [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] and that upregulation of virulence associated genes observed during such exposure is correlated with increased invasion efficiency [13,21].…”
Section: Introductionmentioning
confidence: 99%
“…The outcome of such a co-existence depends on the relative physiological and metabolic attributes as well as the environmental conditions, which concomitantly define the relative population dynamics of the members of the microecosystem. The effect that such co-existence may have on the transcription of virulence-associated genes and invasiveness of the pathogen, has been only marginally studied [18][19][20][21][22][23][24][25]; in some cases, a correlation between the transcriptomic response of the pathogen and its invasiveness has been suggested [6,25].…”
Section: Introductionmentioning
confidence: 99%